2004
DOI: 10.1002/rcm.1777
|View full text |Cite
|
Sign up to set email alerts
|

A novel liquid chromatography/tandem mass spectrometry based depletion method for measuring red blood cell partitioning of pharmaceutical compounds in drug discovery

Abstract: A novel liquid chromatography/tandem mass spectrometry (LC/MS/MS)-based depletion method for measuring compound partitioning between human plasma and red blood cells (RBC) in a drug discovery environment is presented. Conventionally, RBC partitioning is determined by separate measurements of drug concentrations in equilibrating plasma and whole blood or RBC using separate standards prepared in their respective matrices, i.e., in plasma and whole blood or RBC lysates. The process is very tedious, labor-intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 23 publications
2
53
0
Order By: Relevance
“…Blood to plasma concentration ratio (R B ) was determined following incubation in fresh whole blood as described previously. 22) R B values were 1.23±0.06 and 0.88±0.14 for streptochlorin and HIS, respectively. Fraction unbound in blood ( f ub ) was calculated as follows:…”
Section: Methodsmentioning
confidence: 93%
“…Blood to plasma concentration ratio (R B ) was determined following incubation in fresh whole blood as described previously. 22) R B values were 1.23±0.06 and 0.88±0.14 for streptochlorin and HIS, respectively. Fraction unbound in blood ( f ub ) was calculated as follows:…”
Section: Methodsmentioning
confidence: 93%
“…Blood-to-plasma ratios were determined in fresh mouse, rat, dog, and human blood using the indirect method (Yu et al, 2005); compounds were incubated for 0.5 hour at a concentration of 1 mM.…”
Section: Methodsmentioning
confidence: 99%
“…S. Yu et al reported a method for measuring compound partitioning between human plasma and red blood cells (RBC) in a drug discovery field with LC-MS/MS-based depletion assay. 10 The information on the partitioning of a compound of pharmaceutical interest in RBC is important in understanding the pharmacokinetics and pharmacodynamics of the compound and is sometimes critical in screening candidates of a drug without a lost opportunity.…”
Section: 5mentioning
confidence: 99%